Emerging Challenges for Experimental Mechanics in Energy and Environmental Applications, Proceedings of the 5th International Symposium on Experimental Mechanics and 9th Symposium on Optics in Industry (ISEM-SOI), 2015 - Martínez-García, Amalia; Furlong, Cosme; Barrientos, Bernardino; Pryputniewicz, Ryszard J. (Conference Proceedings of the Society for Experimental Mechanics Series,, 2017)
This book contains papers of the 5th International Symposium on Experimental Mechanics (5-ISEM) and the 9th Symposium on Optics in Industry (9-SOI), whose general theme is Emerging Challenges for Experimental Mechanics in Energy and Environmental Applications. These symposia are organized by Centro de Investigaciones en Optica (CIO) and Mexican Academy for Optics (AMO), under the sponsorship of the Society of Experimental Mechanics (SEM) and other national and international Organizations; Symposia are interdisciplinary forums for engineers, technicians, researchers and managers involved in all fields of Optics, Opto-mechatronics, Mechanics and Mechanical Engineering. · Addresses a broad readership including graduate and postgraduate students, researchers, and engineers working in experimental mechanics and in the application of optical methods · Covers a broad spectrum of topics highlighting the use of optical methods in experimental mechanics, energy, and in the environment.